(untitled) (Global Journal of Human-Social Science, 2014)
The Mau Ogiek, an ethnic minority, hunter and gatherer group, wear their indigenous dress to-date. African culture has faced physical and psychological destruction and demonization by non-Africans. Due to psychological destruction of African dress, African Clothing and Textiles scholars have failed to study the dress, resulting in scarce literature on indigenous dress. This paper discusses how the Mau Ogiek apply their non-material culture on their ethnic dress. The research design was hermeneutic discursive interview. The study area was the Mau Forest Complex, Nessuit location with a population of 2600 adult Mau Ogiek people. Judgement sampling was employed to select the sample of 84 consultants. Data were collected by key-consultant in-depth interviews and focus group discussions (FGDs), augmented by photography and observation. Thematic analysis was employed in the interviews and FGDs. Qualitative content analysis was conducted on the photographs and dress collections. Folkways dictate men to fasten oguri et op poinet on the right shoulder. Mores require women to conceal their bodies, thus leginjus extends from the chest to the calves. Clothing customs distinguish the genders through mwenigg op itig and ilmintoisieg. The economic value entails constructing oguriet op inderit from hyrax skin.